Influence of family education style on psychological distance between family members - Iryna I. Ignatieva, Tatiana N. Tretiakova, Kateryna P. Lazor, Yasmina D. Korokhod, (Opción, 2019)
The purpose of this study is to determine the dependence of the length of psychological distance on the style of family education. To achieve the goal, the following methods were used: 1. The method of measuring psychological distance; 2. The sovereignty of psychological space questionnaire 3. Test - questionnaire of parental attitudes towards children (ORO). As a result, the educational impact is a necessary element in the formation of the personality of the adolescent. In conclusion, targeted parental education will help the parents correct their behavior with a teenager.